AKTIVASI PEMAKAIAN JINTEN HITAM (Nigella sativa) TERHADAP RESPONS IMUN PADA GIGI YANG MENGALAMI INFLAMASI - Ningtyas, Endah Aryati Eko (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Exposing pulp tissue will be followed by inflammation reaction, such as releasing host response products. Host response product can cause pain, such as histamine, bradikinin, serotonin and prostaglandin. Nigella sativa contain some components that support immune system. The most component are thymoquinone, dithymoquinone, thymohydroquinone and thymol. Aim of this study ia to know effect of Nigella Sativa to immune response of inflammation tooth. Thymoquinon in Nigella sativa will induce lymphocyte activity. T lymphocyte will induce T helper, T suppressor, and T toxicity forming. They will play role in phagocytosis process.